2005
DOI: 10.1021/bm050663e
|View full text |Cite
|
Sign up to set email alerts
|

Biodendrimer-Based Hydrogel Scaffolds for Cartilage Tissue Repair

Abstract: Photo-crosslinkable dendritic macromolecules are attractive materials for the preparation of cartilage tissue engineering scaffolds that may be optimized for in situ formation of hydrated, mechanically stable, and well-integrated hydrogel scaffolds supporting chondrocytes and chondrogenesis. We designed and synthesized a novel hydrogel scaffold for cartilage repair, based on a multivalent and water-soluble tri-block copolymer consisting of a poly(ethylene glycol) core and methacrylated poly(glycerol succinic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
186
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(189 citation statements)
references
References 47 publications
1
186
0
2
Order By: Relevance
“…By esterifying the dendrimers with succinic acid monomethylallyl ether, and photochemically polymerizing the alkenes, soft gels were produced [213]. These materials are used as corneal adhesives [215,216] and for cartilage repair [217,218]. Scheme 51.…”
Section: The Use Of Other Aliphatic Dendronsmentioning
confidence: 99%
“…By esterifying the dendrimers with succinic acid monomethylallyl ether, and photochemically polymerizing the alkenes, soft gels were produced [213]. These materials are used as corneal adhesives [215,216] and for cartilage repair [217,218]. Scheme 51.…”
Section: The Use Of Other Aliphatic Dendronsmentioning
confidence: 99%
“…In another study, Chung et al noticed that a higher macromer concentration potentially compromised cell viability and growth (Chung et al, 2006). Besides, a higher polymer concentration also resulted in a decreased accumulation of matrix components such as proteoglycans and collagen type II (Sontjens et al, 2006). Recent studies showed that the degradation properties of the gels may have a significant influence on the matrix production and distribution as well.…”
Section: Factors Influencing Cartilage Regenerationmentioning
confidence: 99%
“…We are synthesizing and evaluating dendrimers composed of natural metabolites such as glycerol and succinic acid for medical uses (34)(35)(36)(37)(38)(39). We have found that crosslinkable derivatives of these dendrimers are useful for the repair of ophthalmic wounds and articular cartilage (35,37,(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
“…We have found that crosslinkable derivatives of these dendrimers are useful for the repair of ophthalmic wounds and articular cartilage (35,37,(40)(41)(42). Recently, we described the encapsulation characteristics of a poly(glycerol-succinic acid) (PGLSA) dendrimer and the use of this macromolecule as a potential vehicle for drug delivery (43).…”
Section: Introductionmentioning
confidence: 99%